No dogs allowed! - Wallace, Bill (New York : Holiday House, 2004)
Twelve-year-old Kristina, still struggling to come to terms with the death of her beloved horse, finds it difficult to accept the new dog she receives for her birthday.
Keywords: Dogs; Grief; Pets; Death; Friendship; Family life